Implementasi Algoritme Weighted Least Connection Berbasis Agen Pada POX Controller Untuk Load Balancing Web Server Pada Software Defined Network - Getdra Saragih Sumbayak; Heru Nurwarsito; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Internet users are increasing, causing access demands to a service to increase, which results in the possibility of overloading the server as well. This problem can solve with load balancing technology. The development of network architecture now leads to the Software Defined Network (SDN) because SDN is a architecture that is manageable, dynamic, cost-effective, and adaptable. Previous research has applied load balancing technology on SDN networks using the weighted least-connection algorithm. However, the research still uses flow, which has expired time. In other studies that use the least connection algorithm (LCA) have overcome the problem of expired flow using psutil agents. But the results of the study showed very high CPU usage and unstable traffic distribution. Therefore, this study will apply the psutil agent-based method to the Load Balancing system on SDN networks using the weighted least connection (WLCA) algorithm and determine the performance of the agent-based method. The functional test results show that the psutil agent can send the value of the information on the number of connections on the server to the controller with an error value of 0%. The application of the psutil agent to the weighted least connection algorithm is also better. In testing 500 requests, the response time of WLCA was 29ms while at LCA was 33ms, the value of memory utilization in WLCA was 20.9% while LCA was 21% and the value of CPU utilization in WLCA was 81.2% while at LCA is 84.3%. On the other side, on the 300 and 500 request tests, WLCA algorithm traffic distribution is more stable compared to the LCA algorithm.